Melatonin entrainment of the circadian N-acetyltransferase rhythm in the newborn rat pineal gland - Trávnícková, Z; Illnerová, H (Journal of pineal research, 1997)
In 15-day-old control and vehicle-treated rats, the evening rise of the pineal N-acetyltransferase occurred at the same time as in their mothers, whereas in 5-day-old pups, the rise occurred by 2-3 hr earlier. Four-day administration of melatonin in the late day phase advanced the N-acetyltransferase rise in 15-day-old rats as compared with the rise in the vehicle-treated animals; a slight melatonin induced phase advance in 5- and 27-day-old rats was not significant. The data indicate that the newborn rat's circadian pacemaker controlling the rhythmic N-acetyltransferase rise may be entrained by exogenous melatonin. It appears, however, that the maternal melatonin transferred via milk cannot entrain the pup's pacemaker by phase advancing it, since the N-acetyltransferase rise in the pups begins earlier or at the same time as maternal melatonin production driven by the N-acetyltransferase rhythm.
Keywords: antioxidancia; Animals, Newborn; Rats, Wistar; Pineal Gland; Pregnancy; těhotenství; potkani Wistar; melatonin; novorozená zvířata; cirkadiánní rytmus; Melatonin; Circadian Rhythm; krysa rodu Rattus; Animals; ženské pohlaví; epifýza mozková; Antioxidants; zvířata; Rats; arylamin-N-acetyltransferasa; Arylamine N-Acetyltransferase; Female; Injections, Subcutaneous; injekce subkutánní